2023
DOI: 10.1177/02601060231187511
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on Mediterranean diet adherence: A narrative systematic review

Abstract: Background The COVID-19 pandemic upended many aspects of daily life. For some individuals, this was an opportunity to re-evaluate their life and make better choices, while others were overwhelmed with stressors, leading to a deterioration in mental and physical health. Aim The aim of this narrative systematic review is to explore the effects of the COVID-19 pandemic on Mediterranean diet adherence. Methods A systematic literature search was carried out on PubMed, Scopus and Web of Science electronic databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 111 publications
1
3
0
Order By: Relevance
“…In this sense, we have observed that most of the participants reported not having changed their MedDiet adherence during confinement, which has been rarely reported in previous articles [52]. This fact could well be attributed to the support provided by the PREDIMED-Plus fieldworkers to the participants and the empowerment of participants due to the knowledge acquired during the intervention [53]. Lastly, our results provide new evidence regarding gender inequalities during the COVID-19 pandemic, an important and understudied topic.…”
Section: Discussionsupporting
confidence: 70%
“…In this sense, we have observed that most of the participants reported not having changed their MedDiet adherence during confinement, which has been rarely reported in previous articles [52]. This fact could well be attributed to the support provided by the PREDIMED-Plus fieldworkers to the participants and the empowerment of participants due to the knowledge acquired during the intervention [53]. Lastly, our results provide new evidence regarding gender inequalities during the COVID-19 pandemic, an important and understudied topic.…”
Section: Discussionsupporting
confidence: 70%
“…The degree of adherence to the Mediterranean diet, one of the most healthful dietary patterns, during the COVID-19 pandemic was examined in some studies conducted mostly in Mediterranean countries and a few in non-Mediterranean countries [ 68 ]. As summarized in recent systematic reviews [ 69 , 70 ], results were heterogeneous depending on several potential factors including the methods to assess Mediterranean diet adherence, the use of different thresholds of adherence, and the study countries. In agreement with the systematic review by Della Valle et al [ 69 ], which considered only studies that used validated scales of adherence to the Mediterranean diet, the overall results point to an increased adherence to the Mediterranean diet and/or an increased intake of typical Mediterranean diet foods.…”
Section: Resultsmentioning
confidence: 99%
“…There are several risk factors for COVID-19, including dietary style and lifestyle [ 21 ]. Indeed, an increased risk of severe COVID-19 has been observed in patients following the Western diet, which provides a high intake of saturated fats, sugars, and refined carbohydrates [ 24 ]. This dietary pattern is known to dysregulate the immune response and impair the host’s defense against viruses [ 25 ], stimulating the expression of pro-inflammatory cytokines leading to cytokine storm [ 26 ].…”
Section: Discussionmentioning
confidence: 99%